ANTI SUPPORT STRONG DOMATIC PARTITION OF A FUZZY GRAPH - K. M. DHARMALINGAM, M. REVATHI (Asian Journal of Current Engineering and Maths, 2016)
Let G = (; ) be a fuzzy graph. Let u be an element of V. Let N(u) = v âˆˆ V : (uv) = (u) âˆ§ (v). The fuzzy support of u is dened as the sum of the neighborhood degrees of the elements in N(u). In this research work we introduce the concept of Anti Support strong domatic partition of a Fuzzy graphs. The fuzzy support of a vertex is dened and domination based on the fuzzy support is considered. Several results involving this new fuzzy domination parameter are established. we also obtain the Anti fuzzy Support strong domatic number of G and is denoted by d s f(supp)(G).